Eradicating tumor in a recurrent cervical cancer patient with autologous tumor-infiltrating lymphocytes and a modified lymphodepleting regimen. Issue 2 (17th February 2022) - Guo, Jing; Luo, Ning; Ai, Guihai; Yang, Weihong; Zhu, Jihui; Li, Caixia; Chen, Rong; Zhang, Changbao; Liu, Shupeng; Jin, Huajun; Cheng, Zhongping
Abstract : Tumor-infiltrating lymphocyte (TIL) therapy has shown promising results against several cancers. However, traditional lymphodepleting regimens are severe and represent a major limitation for a more widespread use of TIL. The modified pretreatment strategies may alleviate side effects and demonstrate the persistence of tumor-reactive T cells in the blood. Here, we report a case who was diagnosed recurrent cervical cancer with bladder metastasis. Omitting high dose of IL-2, she received intravenous dose of cyclophosphamide (20 mg/kg) for 3 days, approximately 48 hours before receiving the intravenous infusion of TILs. Half dosage (100 mg) of PD1 antibody was administered with purpose of neutralizing PD1 expressed on T cells surface. She achieved complete response 10 weeks after one-time TILs infusion. Adverse reactions were negligible and safely manageable in a general ward without the need for intervention from intensive care units. Time-course peripheral blood counts and TCR repertoire sequencing demonstrated a robust expansion and long-term persistence of the infused TILs. These results illustrated the potential value of modified lymphodepletion, followed by TILs for the treatment of patients with cervical cancer with local recurrence. Trial registration number, NCT04766320 .